A Novel Homozygous Nonsense Mutation p.Cys366* in the WNT10B Gene Underlying Split-Hand/Split Foot Malformation in a Consanguineous Pakistani Family - Khan, Amjad; Wang, Rongrong; Han, Shirui; Umair, Muhammad; Alshabeeb, Mohammad A.; Ansar, Muhammad; Ahmad, Wasim; Alaamery, Manal; Zhang, Xue (Frontiers in Pediatrics, 2020)
Abstract Split hand/split foot malformation (SHFM) or ectrodactyly is characterized by a deep median cleft of the hand or foot, hypoplasia or aplasia of the metacarpals, metatarsals, and phalanges. It is a clinically and genetically heterogeneous group of limb malformations. This study aimed to identify the pathogenic variant in a consanguineous Pakistani family with autosomal recessive SHFM. Peripheral blood samples were obtained, DNA was extracted, WNT10B coding and noncoding regions were PCR amplified and Sanger sequencing was performed using workflow suggested by Thermo Fisher Scientific. A novel homozygous nonsense variant (c.1098C>A; p.Cys366*) was identified in the WNT10B gene in the index patients, which probably explains SHFM type 6 in this family in comparison with similar data from the literature.